Effectiveness of Proximal Landing Zones 0, 1, and 2 Hybrid Thoracic Endovascular Aortic Repair: A Single Centre 12 Year Experience. (March 2022) - Kudo, Tomoaki; Kuratani, Toru; Shirakawa, Yukitoshi; Shimamura, Kazuo; Kin, Keiwa; Sakamoto, Tomohiko; Shijo, Takayuki; Watanabe, Yoshiki; Masada, Kenta; Sakaniwa, Ryoto; Sawa, Yoshiki
Abstract : Objective: Hybrid thoracic endovascular aortic repair (TEVAR) is being accepted increasingly as a first line treatment for arch repair at the present authors' institution. This study aimed to clarify the effectiveness of zones 0, 1, and 2 landing hybrid TEVAR. Methods: This was a retrospective single centre case series. From April 2008 to March 2020, 348 patients (median age 72 years; interquartile range [IQR] 65, 77 years) were enrolled, with a median follow up period of 5.6 years (IQR 2.6, 8.7 years). The procedures included zone 0 in 135 patients (38.8%), zone 1 in 82 patients (23.6%), and zone 2 proximal landing zone (LZ) hybrid TEVAR in 131 patients (37.6%). The pathologies consisted of dissecting aortic aneurysms in 123 (35.3%) patients. Emergency procedures were performed in 39 (11.2%) patients. Results: The 30 day mortality ( n  = 2, 0.6%) and hospital deaths ( n  = 6, 1.7%) were registered. The stroke rate was 1.1% ( n  = 4), while early and late endoleak rates were 4.8% ( n  = 17) and 1.7% ( n  = 6), respectively. Type 1a endoleak and retrograde type A dissection occurred in seven (2.0%) and three (0.9%) patients, respectively. The cumulative survival, freedom from aorta related deaths, and freedom from aortic events in 10 years were 75.0%, 97.2%, and 84.1%, respectively. The freedom from aortic events in each landing zone in 10 years was 82.3%, 81.4%, and 87.9% for zones 0, 1, and 2, respectively. The 10 year survival rates were 82.5% and 73.6%; the 10 year aorta related death free rates were 94.9% and 98.6%, and the 10 year aortic event free rates were 82.3% and 85.5% in the zone 0 and zone 1 and 2 TEVAR, respectively. Conclusion: Satisfactory early and long term results of hybrid arch repair at zones 0, 1, and 2 were achieved. To avoid complications and aortic events, the treatment strategy of hybrid arch repair for aortic arch pathologies should be tailored using accurate pre-operative assessment of the ascending aorta and the aortic arch.